MODEL PERIODIK DAN STOKASTIK DATA PASANG SURUT JAM-JAMAN DARI PELABUHAN PANJANG - Ahmad Zakaria (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2015)
The aim of this study are intended to compare periodic and stochastic tide models generated by using FFT frequencies and astronomic frequencies. The Fourier series are used to simulated peri- odic model, and the autoregressive method is employed to simulate stochastic model. 253 domi- nant FFT frequencies and 9 astronomic frequencies are used as constituent frequencies to simulate periodic models. 512 hours of data are used for the model. Results of this study present that the periodic and stochastic models using the FFT frequencies give more accurate results than periodic and stochastic models by using the astronomic frequen - cies.